Survival of Rhizobium in flooded soils - De-Polli, Helvécio; Franco, Avilio A.; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
In two greenhouse experiments the effect of periodic innundation on survival of native and inoculated Rhizobium and its effect on nodulation and nitrogen fixation of Centrosema pubescens and soybean (Glycine max) variety Santa Maria were studied. The first experiment included two lowland soils maintained at 3 moisture levels (field capacity, flooded at soil level and flooded 5 cm above) for four periods (0, 25, 50 and 100 days). Centrosema was planted after draining at the end of each moisture period. Nodule numbers were reduced by previous flooding of the soil. In one of the soils (Seropédica) nodulation and plant growth decreased with increasing moisture periods while they increased until 25 days in the other soil (Piranema), after which the similar decrease was observed. In the soil Seropédica, the inoculated strains, identified by the black nodules they produced, were more sensitive to excessive humidity than the native soil strains. In the second experiment nodulation and nitrogen fixation of soybean variety Santa Maria (flood tolerant) was compared at three moisture levels (75, 100 and 125 percent of field capacity) in the same two soils. Humidity levels used did not affect the soybean symbiosis and inoculation was as efficient as mineral nitrogen (240 kg/ha) at all moisture levels. In soils with poor drainage it seems more important to inoculate legumes property than in normal soils.